2013
DOI: 10.1186/cc12567
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of blood-glucose measurements using glucose meters and arterial blood gas analyzers in critically ill adult patients: systematic review

Abstract: IntroductionGlucose control to prevent both hyperglycemia and hypoglycemia is important in an intensive care unit. Arterial blood gas analyzers and glucose meters are commonly used to measure blood-glucose concentration in an intensive care unit; however, their accuracies are still unclear.MethodsWe performed a systematic literature search (January 1, 2001, to August 31, 2012) to find clinical studies comparing blood-glucose values measured with glucose meters and/or arterial blood gas analyzers with those sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
75
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(87 citation statements)
references
References 40 publications
1
75
0
5
Order By: Relevance
“…Plasma glucose values by capillary point-of-care testing have been found to be potentially inaccurate, with frequent false elevations [479][480][481] over the range of glucose levels, but especially in the hypoglycemic and hyperglycemic ranges [482] and in shock patients (receiving vasopressors) [478,480]. A review of studies found the accuracy of glucose measurements by arterial blood gas analyzers and glucose meters by using arterial blood significantly higher than measurements with glucose meters using capillary blood [480].…”
Section: We Suggest the Use Of Arterial Blood Rather Than Capillary Bmentioning
confidence: 99%
“…Plasma glucose values by capillary point-of-care testing have been found to be potentially inaccurate, with frequent false elevations [479][480][481] over the range of glucose levels, but especially in the hypoglycemic and hyperglycemic ranges [482] and in shock patients (receiving vasopressors) [478,480]. A review of studies found the accuracy of glucose measurements by arterial blood gas analyzers and glucose meters by using arterial blood significantly higher than measurements with glucose meters using capillary blood [480].…”
Section: We Suggest the Use Of Arterial Blood Rather Than Capillary Bmentioning
confidence: 99%
“…The recommendation presented for this CQ was based on the results of a systematic review conducted by Inoue et al 336. In a comparison of measurements taken using a glucometer with capillary blood or a blood gas analyzer using arterial blood, measurements taken using the arterial blood gas analyzer were less likely to include measurement errors falling significantly outside the acceptable range (odds ratio: 0.04; 95% confidence interval [CI]: 0.01–0.14) 336.…”
Section: Cq14: Blood Glucose Managementmentioning
confidence: 99%
“…In a comparison of measurements taken using a glucometer with capillary blood or a blood gas analyzer using arterial blood, measurements taken using the arterial blood gas analyzer were less likely to include measurement errors falling significantly outside the acceptable range (odds ratio: 0.04; 95% confidence interval [CI]: 0.01–0.14) 336. In addition, in a comparison of glucometer measurements using capillary blood or arterial blood, the risk of measurement error was significantly lower when arterial blood was used (odds ratio: 0.36; 95% CI: 0.25–0.52).…”
Section: Cq14: Blood Glucose Managementmentioning
confidence: 99%
“…Third, Daviaud et al measured glucose levels using capillary glucometers; however, these devices have been shown to have a low accuracy in critically ill patients when compared to glucose measurements performed on venous/arterial blood. In particular, mean differences with the blood values may vary from 0.2 to 1.4 mmol/L (limits of agreement from 1.7 to 2.5 mmol/L), especially within the hypoglycaemic range [16]. Also, the use of vasopressors and the presence of oedema, both of which are common after CA, were important determinants of inaccuracy and might increase the risk of errors of capillary glucometers in this setting.…”
mentioning
confidence: 99%